2008
DOI: 10.1016/j.ehb.2008.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Historical trends in height, weight, and body mass: Data from U.S. Major League Baseball players, 1869–1983

Abstract: We employ a unique dataset of Major League Baseball (MLB) players -a select, healthy population -to examine trends in height, weight, and body mass in birth cohorts from 1869 to 1983. Over that 115-year time period, U.S. born MLB players have gained, on average, approximately 3 in. (7.6 cm) in height and 27.0 lb (12.2 kg) in weight, which has contributed a 1.6-unit increase in the body mass index. Where comparable data are available, U.S. born MLB players are about 2.0 in. (5.1 cm) taller and 20.0 lb (9.1 kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Our findings for Major League Baseball Players with respect to height, weight and BMI, are in agreement (although slightly higher) with Saint Onge et al [32]. Like those researchers, we also found that heights of players born after WWII increased at a slower rate than those born before the war.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings for Major League Baseball Players with respect to height, weight and BMI, are in agreement (although slightly higher) with Saint Onge et al [32]. Like those researchers, we also found that heights of players born after WWII increased at a slower rate than those born before the war.…”
Section: Discussionsupporting
confidence: 93%
“…The will be absent from the remaining bouts. 9 http://sumodb.sumogames.de/Default.aspx table also shows that the BMI in the later period was 5.7 points higher than in the early period, which is in line with other professional sports (Saint Onge et al, 2008). Table 3 compares mean values between domestic Japanese wrestlers and foreign wrestlers.…”
Section: Datasupporting
confidence: 55%
“…The BMI is calculated from a person's weight and height, and is a reliable indicator of body fatness for adults 6 . In the field of economics, the BMI is generally used to capture the degree of fatness (e.g., Zellner et al, 2004;Chrzanowska et al, 2007;Vignerova et al, 2007;Saint Onge et al, 2008;Yamamura 2012). Although a higher BMI can benefit a sumo wrestler, it also increases the probability of injury, thus lowering performance.…”
Section: Methodsmentioning
confidence: 99%
“…Secular trend could be followed up in the performance level, as well, as stuctural development of the body and the accelerated maturation could help with improving physical capacity [38]. We also have some published [39,40] and unpublished experience about the existence of positive secular trend among Hungarian athletic children e.g. in basketball, where the body height is the key component in the selection.…”
Section: Introductionmentioning
confidence: 99%